PENGARUH KOMBINASI DOSIS PUPUK NITROGEN DAN KOMPOS JERAMI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) KULTIVAR BISMA - Amran Jaenudin; Umi Trisnaningsih; Yoyoh Rohayati (Agroswagati Jurnal Agronomi, 2016)
This research aimed to determine: (1) the effect of a combination dose of nitrogen fertilizer and straw compost on growth and yield of corn (Zea mays L.) cultivars Bisma and (2) dose combination of nitrogen fertilizer and straw compost that gives the best results on the growth and yield of corn (Zea mays L.) cultivars Bisma. The experiment was conducted in UPTD Balai Pengembangan Benih Palawija (BPBP) at Plumbon Cirebon Jawa Barat, from March through the month of June 2015. The method used in this research was the experimental method. The experimental design used was a randomized block design (RBD). This experiment consisted of 9 combined treatment nitrogen fertilizer and straw compost, each repeated three times, so there are 27 experimental plots. The combination treatment was tested in the field are: A (50 kg urea/ha and straw compost 10 tons/ha), B (50 kg urea/ha and straw compost 15 tons/ha), C (50 kg urea/ha and straw compost 20 tons/ha), D (100 kg urea/ha and straw compost 10 tons/ha), E (100 kg urea/ha and straw compost 15 tons/ha), F (100 kg urea/ha and straw compost 20 tons/ha), G (150 kg urea/ha and straw compost 10 tons/ha), H (150 kg urea/ha and straw compost 15 tons/ha), and I (150 kg urea/ha and straw compost 20 tons/ha). The results of research showed that: (1) there are significantly effect between dose combination of nitrogen fertilizer and straw compost on plant height age of 28, 35, and 42 Days After Planting (DAP), number of leaves per plant age of 35 and 42 DAP, stem diameter age of 35 and 42 DAP , Shoot Root Ratio (SSR) age of 28, 35, and 42 DAP, N uptake, Leaf Area Index, weight without husk the best cobs per plant and per plot , and weight dry shelled per plant and per plot and (2) dry shelled weight per plot gave by the combination treatment of nitrogen fertilizer 150 kg/ha and straw compost 20 tons/ha which produces 4.66 kg/plot or the equivalent of 5.92 tons/ha, assuming 80 % effective land.